Catching the rebound: Economy-wide implications of an efficiency shock in the provision of transport services by households - Simon Koesler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We investigate the rebound effect of a 10% energy cefficiency improvement in the provision of private transport services by German households. In the process, we take into account that household behaviour may be influenced by habits, build on a detailed representation of the provision of private transport services, and disentangle the direct and indirect rebound effect. Our analysis shows that rebound has the potential to significantly reduce the expected energy savings of an energy efficiency improvement at households. In particular if households have a flexible demand structure, rebound can erode large parts of efficiency increases. Household habits have an initial detrimental effect on rebound. They limit the ability of households to adapt to changes in the prevailing price and income system and therewith temporally block parts of the channels that lead to rebound. In the long run, however, if habits are formed on the basis of historic consumption, habits do not affect rebound. In isolation, the direct and indirect rebound effect of the efficiency shock are positive, but direct rebound is much stronger.
urn:nbn:de:bsz:180-madoc-351030
Keywords: D13; D58; Q41; Q43; 330; rebound; efficiency improvement; energy efficiency; habits